Measuring children's perceptions of their use of the Internet: A rasch analysis - Johnson, Genevieve; Cavanagh, Rob (Australian Association for Research in Education (AARE), 2012)
Measuring children’s use of emerging technologies is prerequisite to determining the effect of such use on children’s health, development and learning. The Ecological Techno-Microsystem provides a theoretical foundation upon which to select test items appropriate to the measurement of children’s self-reported use of the internet across home, school and community contexts. A 15 item rating scale was developed which included five items across the three environments, for example: 1) I use the internet at home; 2) I use email at school; 3) I instant message at home; 4) At home, I use the internet to play games; 5) I visit websites when I am at somebody else’s house. Ninety children rated each of the 15 items on a four-category response scale. Individual item fit statistics confirmed that data from all 15 items fitted the model well. Differential Item Functioning, consistent with empirical evidence, suggested gender differences in patterns of internet use during childhood. Rasch analysis (i.e., Item Map) confirmed that children with the highest self-reported internet use scores on the 15 item rating scale affirmed the most difficult items, that is, the items to which the that fewest children responded in the affirmative.